The TMJ handbook : a therapeutic guide to relieving jaw tension and pain with yoga and mindfulness - Shachoy, Cator (Shambhala Publications, Inc., 2024)
"Alleviate TMJ pain with a powerful, integrative mind-body program that draws on yoga, mindfulness, and craniosacral bodywork, and includes 75 instructional movements and audio downloads. In The TMJ Handbook, Cator Shachoy explains the anatomy and physiology of Temporomandibular Joint Dysfunction (TMD)- what we commonly refer to as "TMJ." She unpacks the physical, emotional, and energetic reasons why this pain can occur and become so debilitating-incuding injury, stress and tension, emotional trauma, grief and rage, hormonal imbalances, among other causes. She then offers a unique and effective approach to reducing TMJ pain that combines yoga, massage, meditation, and craniosacral therapy. The TMJ Handbook delves into: A definition and explanation of jaw tension and jaw anatomy Headaches, stress, and trauma Conscious healing touch and self-massage Yoga poses and sequences Shachoy shares inspiring and instructive stories of patients she has treated and empowers us with the knowledge and skills to help ourselves. This fully illustrated guide has seventy-five instructional movements and audio downloads of exercises and meditations"--